Solid-phase supported design of carriers for therapeutic nucleic acid delivery - Krhac Levacic, Ana (Biosci Rep, 2017)
Nucleic acid molecules are important therapeutic agents in the field of antisense oligonucleotide, RNA interference, and gene therapies. Since nucleic acids are not able to cross cell membranes and enter efficiently into cells on their own, the development of efficient, safe, and precise delivery systems is the crucial challenge for development of nucleic acid therapeutics. For the delivery of nucleic acids to their intracellular site of action, either the cytosol or the nucleus, several extracellular and intracellular barriers have to be overcome. Multifunctional carriers may handle the different special requirements of each barrier. The complexity of such macromolecules however poses a new hurdle in medical translation, which is the chemical production in reproducible and well-defined form. Solid-phase assisted synthesis (SPS) presents a solution for this challenge. The current review provides an overview on the design and SPS of precise sequence-defined synthetic carriers for nucleic acid cargos.